Effect of micron-scale pores increased by nano-SiO2 sol modification on the strength of cement mortar - Xu Yaoqun; Wang Juan; Zhang Peng; Guo Jinjun; Hu Shaowei (Nanotechnology Reviews, 2022)
A study was conducted through quantitative calculations on the correlation between the micron-scale pores and the strength of nano-SiO2 (NS) sol reinforced cement mortar. The strength, pore structure, and microstructure of NS sol modified mortar were investigated, and the mortars were made equivalent to a two-phase material comprised of pores and mortar matrix; the model was applied to conduct a quantitative analysis of the correlation between pores and the strength. According to the research results, the modification made to the mortar using the NS sol led to significantly increased early strength and the level of porosity was also increased. Furthermore, the addition of NS caused a change to the C–S–H gel morphology of cement hydration products. As revealed by the results of quantitative analysis, the addition of 1.5 and 3% NS improved the mortar matrix strength by 29.3 and 56.6%, respectively. Moreover, the ratio between the mortar strength (f c) and matrix strength index (K) exhibited a nonlinear correlation with the porosity negatively. It was thus inferred that the increase in mortar porosity inhibited the improvement of mortar strength under the influence of NS sol.